E-LEARNING SEBAGAI MEDIA PEMBELAJARAN: (Studi Kasus: STBA TECHNOCRAT TANGERANG) - Linda Apriyanti; Surdi Supriyadi; Yus Jayusman (Jurnal Teknologi Informasi dan Komunikasi, 2021)
The implementation of e-learning helps students facilitate the learning process if they cannot attend class. STBA Technocrat has not yet utilized e-learning technology for learning media. Many lecturers and students at STBA Technocrat are private employees. Therefore, creating an e-learning platform for learning media is essential. To achieve these objectives, the author uses a research method approach that includes field studies, literature reviews, and system development and design using the waterfall and UML models, with PHP and MySQL programming languages. In conclusion, e-learning can significantly aid lecturers and students in delivering and receiving material, allowing the teaching and learning process to proceed efficiently without being affected by location and time.